Non-invasive measurement of muscle compartment elasticity in lower limbs to determine acute compartment syndrome: Clinical results with pressure related ultrasound. Issue 2 (February 2020) - Sellei, R.M.; Wollnitz, J.; Reinhardt, N.; de la Fuente, M.; Radermacher, K.; Weber, C.; Kobbe, P.; Hildebrand, F.
Highlights: Novel method of non-invasive measurement of muscle elasticity. Reliable approach for monitoring imminent acute compartment syndrome. High correlation between the decreasing elasticity and increasing intra-compartmental pressure. Abstract: Purpose: Close monitoring of patients at risk to develop an acute compartment syndrome (ACS) is well known to be essential. There is a relevant risk that clinical assessment alone is not reliable enough. Reliable assessment of the elasticity of the muscle compartment might represent a helpful tool to assess the pressure in this enclosed space. Therefore, the purpose of this study was to determine the feasibility of muscle elasticity measurements by a non-invasive device. Methods: In a prospective study, patients with elevated intra-compartmental pressure (ICP) were included. An ultrasound-based measurement approach was used to determine the relative elasticity (RE) of both, the affected and unaffected limb. A pressure transducing ultrasonic probe head was combined with the probe to obtain cross section views of the anterior tibial compartment and to detect the observer´s amount of pressure applied on the limb surface. The compartment depth without compression (P0 ) corresponds to 100%. The difference to the compartment depth with a probe pressure of 80mmHg (P80 ) on the limb (delta) related to P0 resulted in a value of relative elasticity (%). These values were compared with the invasive needle measurement (mmHg) regarding their intra-individual difference and correlation of the compartmental pressure. Results: In six trauma patients the relative elasticity in their paired limbs showed a significant difference. The RE in the healthy compartments revealed a level of 17.95% (SD+/-5, 4), whereas the RE of the affected limbs significantly decreased to a mean of 5, 14% (SD+/-2, 1) (p < 0, 0001). The average values of the repetitively measured RE and the ICP showed a high level of correlation (spearman correlation coefficient: roh = 0, 929). The RE less than 10, 5% of the anterior tibial compartment had a sensitivity of 95, 8% and a specificity of 87, 5% to an appropriate diagnosis of ACS. Discussion: The presented study appears to represent a promising approach to reliably assess the pressure in a muscle compartment. In this first clinical study, our measurement method represents a low cost, easy and secure approach that has the potential to substitute invasive measurement. Further investigations and development in lager cohorts are required to improve its practicality and to confirm the reliability.